Diffuse idiopathic skeletal hyperostosis, beyond the musculoskeletal system - Fabiola Atzeni; Alessandra Alciati; Shay Brikman; Reuven Mader (Exploration of Musculoskeletal Diseases, 2023)
It has been suggested that diffuse idiopathic skeletal hyperostosis (DISH), a skeletal disease characterized by the ligamentous ossification of the anterolateral spine, is a radiological entity with no clinical implications; however, many patients suffer from chronic back pain, decreased spinal mobility, and postural abnormalities. Additionally, the pathological new bone formation at the cervical and thoracic levels may mainly produce dysphagia and breathing disturbances. Over the last 20 years, a close association between DISH, obesity, diabetes mellitus (DM), and metabolic syndrome (MS) has emerged. However, a causal relationship has not yet been established. It has been suggested that the longer life expectancy and the growing incidence of MS in Western populations, associated with the tendency of DISH to manifest in later life, may increase the DISH prevalence rates in the following decades. Future investigations should focus on the early DISH phase to clarify pathogenetic mechanisms and identify targeted therapies.